PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN BIDANG PERBANKAN (STUDI PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2019). - Apriani Soraya (2021)
his study aims to determine the effect of Managerial Ownership, Institutional Ownership, Audit Committee, Board of Commissioners Size on the value of banking companies listed on the Indonesian stock exchange for the period 2016-2019. This research uses quantitative research methods. This study uses secondary data in the form of financial and annual company reports, with a sample of 14 banking companies. The data analysis technique used is the classical assumption test, multiple regression and hypothesis testing consisting of the t test. Based on the results of data analysis, it can be concluded that (1) Managerial ownership has a significant effect on firm value, (2) Institutional ownership does not have a significant effect on firm value, (3) the Audit Committee does not have a significant effect on firm value, (4) )The size of the Board of Commissioners does not have a significant effect on firm value